1MDB (1 Malaysia Development Berhad), Scandal, and Its Impact on Malaysian Domestic Politics - Ali Maksum (Politika: Jurnal Ilmu Politik, 2020)
This article examines the publicly discussed 1 Malaysia Development Berhad (1MDB) scandal and its impact on Malaysian domestic politics. Following this case, Najib Razak as prime minister of Malaysia was under pressure. This is because of the strong allegation of Najib Razak’s involvement in the 1MDB scandal. This issue became public discourse after the widely report made by New York-based media Wall Street Journal concerning Najib’s abuse on the corporate asset. The scandal not only shakes Najib’s political coalition but also indirectly has provoked public distrust against him including from his political Guru, Mahathir Muhammad. Dr Mahathir openly accuses Najib’s behaviour and declare to quit from his longest loyal party, UMNO. Later on, this scenario has created a new political landscape in Malaysia. Therefore, this article attempts to examine the new Malaysian political landscape specifically the relationship of BN and the opposition vis-à-vis Mahathir political alliance. Nevertheless, history has witnessed that in the last election, Pakatan Harapan won the most dramatical election ever since the independence of Malaysia and UMNO-BN has lost the power. Yet, the political scenario surrounding 1MDB scandal and the relationship between UMNO-BN vis-à-vis other parties became one of the stories that always trigger public discourse, even until today.